CIRCULAR RNA - miRNA MEDIATED INTERACTION IN MYOCARDIAL INFARCTION - Yordanka Doneva; Veselin Valkov; Yavor Kashlov; Galya Mihaylova; Atanas Angelov; Maria Radanova (Peytchinski Publishing, 2021)
Circular RNA (circRNAs) belong to the long non-coding RNA family, but unlike the linear RNA in circular RNA, the 3' and 5' end in the RNA molecule are joined together, forming their circular structure. Until recently, circRNAs have been believed to be a side product of splicing, but now it is known that they have a wide range of biological functions, from regulators of gene expression to regulators of other non-coding RNAs - microRNAs (miRNAs). CircRNAs have the potential of being therapeutic targets and biomarkers for diseases. There are little data and only several investigations about this type of RNAs in myocardial infarction in humans. This review summarizes the role of some new circRNA - miRNA interactions in the development of Myocardial Infarction.